World Wide Video Festival 1987. - Kijkhuis, Den Haag; World Wide Video Festival, Den Haag (Den Haag : Kijkhuis, 1987)
After Image ; Akerman, Chantal ; Anderson, Laurie ; Andre, Marie ; Atlas, Charles ; Barber, George ; Barbier, Dominik ; Bearden, Victoria ; Bigoni, Bruno ; Birnbaum, Dara ; Blumberg, Skip ; Bohm, Hella ; Bourges, Alain ; Bunn, David ; Burki, Marie José ; Cahen, Robert ; Day, Dennis ; Decostere, Stefaan ; Downey, Juan ; Eshetu, Theo ; Feingold, Ken ; Finley, Jeanne C. ; Geller, Matthew ; etc.
World Wide Video Festival 1987, Kijkhuis, Den Haag, 5-12 september 1987
boek